Stilistika Cerpen Lailatun Ghaba ‘Anha al-Qamar Karya Najib al-Kilany - Ramadani, Ranjy (Arabiyatuna: Jurnal Bahasa Arab, 2021)
This study aims to reveal the beauty of the language style in the short story Lailatun Ghaba 'anha al-Qamar by najib al-Kilany through a stylistic perspective. Najib al-Kilany as a writer also has his own style that is interesting to know. This study uses a descriptive method of data analysis by deploying data collection techniques, namely observations and note-taking. The results of this study reveal several stylistic aspects contained in the short story, such as: a semantic aspect which includes the use of at-taraduf (synonym), a syntactic aspect which includes the function of at-taqdim wa at-ta'khir (prioritizing word position and ending it), and an imagery aspect which includes simile, hyperbole, metaphor, and synecdoche styles. Based on the study’s results, it is concluded that Najib al-Kilany emphasizes the imaginary side of a story, which leads the reader to being immersed in his work.